PENINGKATAN KEMAMPUAN PERSUASIF BAGI CALON GURU DALAM PEMBELAJARAN SEBAGAI MISI PEMBENTUKAN KARAKTER PESERTA DIDIK - Sumarta, I Wayan Ardi; Yulistia, Anisa; Karima, Muhammad Kaulan (Education, Language, and Arts: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service is to assist teachers in using persuasive skills to improve their self-image as role models, broaden prospective teachers' insight into the application of persuasive language in learning, and train prospective teachers in using persuasive language in learning activities. Furthermore, the training on the use of persuasive language will implement forms of persuasive language where all training participants can learn through their experiences so that the planned objectives can be achieved optimally. The methods used in this training are lectures, questions and answers, discussions, demonstrations, and assignments. The number of participants in this training is targeted at 30 people. Evaluation in this training will be carried out at the beginning of the training, during the training process, and when the training ends. At the beginning of the training, participants will be given a pre-test. Evaluation during the training process will determine the ability of teachers in using speech acts in learning. The training is considered successful if more than 90% of participants are active during the training process. Furthermore, the evaluation at the end of the training, participants are given the task of creating forms of conversation involving speech acts in learning and then practicing them in the form of peer teaching. Tujuan pengabdian masyarakat ini adalah untuk membantu guru dalam menggunakan keterampilan persuasif untuk meningkatkan citra diri sebagai panutan, memperluas wawasan calon guru tentang penerapan bahasa persuasif dalam pembelajaran, dan melatih calon guru dalam menggunakan bahasa persuasif dalam kegiatan pembelajaran. Lebih lanjut, pelatihan penggunaan bahasa persuasif akan menerapkan bentuk-bentuk bahasa persuasif di mana seluruh peserta pelatihan dapat belajar melalui pengalamannya sehingga tujuan yang direncanakan dapat tercapai secara optimal. Metode yang digunakan dalam pelatihan ini adalah ceramah, tanya jawab, diskusi, demonstrasi, dan penugasan. Jumlah peserta pelatihan ini ditargetkan sebanyak 30 orang. Evaluasi dalam pelatihan ini akan dilakukan di awal pelatihan, selama proses pelatihan, dan setelah pelatihan berakhir. Di awal pelatihan, peserta akan diberikan pre-test. Evaluasi selama proses pelatihan akan menentukan kemampuan guru dalam menggunakan tindak tutur dalam pembelajaran. Pelatihan dianggap berhasil apabila lebih dari 90% peserta aktif selama proses pelatihan. Selanjutnya, pada evaluasi di akhir pelatihan, peserta diberi tugas untuk menciptakan bentuk-bentuk percakapan yang melibatkan tindak tutur dalam pembelajaran dan kemudian mempraktikkannya dalam bentuk peer teaching.